Effect of Additional Apical Preparation on Retreatment of Curved Root Canals Filled with Different Sealers - Tavares, Karina I. M. C.; Pinto, Jader C.; Santos-Junior, Airton O.; Duarte, Marco A. H.; Guerreiro-Tanomaru, Juliane M.; Tanomaru-Filho, Mario (European Journal of Dentistry, 2022)
Objective This study assessed the influence of additional apical preparation on material removal during retreatment of curved root canals filled with different sealers.Materials and Methods Twelve mesial roots of mandibular molars with two separate canals and curvature between 25 and 35 degrees were selected. The working length was established 1-mm short of the apical foramen, and all the root canals were prepared using ProDesign R (PDR) 25/0.06. After preparation, the root canals were divided in two groups (n = 12) and filled by continuous wave condensation technique with NeoMTA Plus or AH Plus. All the root canals were retreated using rotary ProDesign Logic RT 25/0.08, reciprocating PDR 25/0.06 and apical preparation with PDR 35/0.05. Additional apical preparation was performed with ProDesign Logic (PDL) 50/0.01. The samples were scanned using a Skycan 1176 micro–computed tomography (micro-CT), voxel size 8.74 µm, before and after the retreatment procedures. Percentages of remaining filling material were evaluated.Statistical Analysis The data were submitted to paired and unpaired t-tests (α = 0.05).Results Percentage of remaining filling material was similar between the root canals filled with NeoMTA Plus or AH Plus sealer after retreatment using PDR 35/0.05, and after additional apical preparation using PDL 50/0.01 (p > 0.05). However, PDL 50/0.01 significantly decreased the percentage of remaining filling material in the apical third after the additional apical preparation for both sealers (p < 0.05).Conclusion NeoMTA Plus or AH Plus did not influence the retreatment of curved root canals. ProDesign Logic 50/0.01 promoted greater filling material removal in the apical third.
Keywords: retreatment; root canal preparation; root canal filling materials; X-ray microtomography